Wpływ Nieliniowych Charakterystyk Zawieszenia Samochodu na Komfort Jazdy - Piskorz, Z. (Engineering Transactions, 1972)
In the paper is analyzed the influence of the car suspension characteristics on the dispersion of displacements, velocities and accelerations. Knowledge of these factors is necessary in formulating. the criteria of the ride comfort and optimum selection of the suspension parameters. The kinematic forcing of the system investigated is produced by the roughness of the road surface characterized by a correlation function. Applying the correlation theory of stochastic processes the corresponding dispersions for a system with two degrees of freedom are obtained, and in the case of uncoupled vibration - for a system with a single degree of freedom. The graphs of ratios of the corresponding. dispersion of linear and nonlinear systems are finally given.